AN ANALYSIS OF STUDENTS DIFFICULTIES IN WRITING INFORMATIVE ABSTRACTS IN JURNAL ONLINE MAHASISWA UNIVERSITAS RIAU - Cindy Sasnia Putri Ananda Kadir; Eliwarti Eliwarti; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Writing an abstract is one of the important components that must be included in a thesis or research article, but in fact, it is difficult to do. The purpose of this research was to identify difficulties in writing informative abstracts in Jurnal Online Mahasiswa Universitas Riau. This research used a qualitative approach, and the research design is content or document analysis. The data was taken from 40 Jurnal Online Mahasiswa Universitas Riau in the last 4 years (2019–2022). The results showed that the percentage of rhetorical moves in Move 1 (Introduction) was 20%, Move 2 (Purpose), Move 3 (Method), and Move 5 (Conclusion) was 97.5%, while Move 4 (Product) was 95%. Furthermore, in the writing aspects, there are 80% of documents that use formal vocabulary, formal verbs, and full verbs. Then, only 47.5% of the documents use formal grammar structures; 77.5% of the abstracts used statements; 52.5% use impersonal language; 62.5% of the abstracts analyzed were precise; 75% use hedging statements; and 70% of the abstracts used transition words. The conclusion is that there are difficulties in writing an abstract framework in move 1 (introduction), and formal grammar structure is the most difficult writing aspect that students experienced.Key Words: Difficulty, Informative Abstract, Writing